PET and PET/CT : a clinical guide - Lin, Eugene; Alavi, Abass (Thieme, 2019)
Top-selling, concise guide to PET and PET/CT imaging from distinguished radiologists, now in a new edition! PET and PET/CT have been increasingly used as effective imaging modalities in the management of patients with cancer, neurologic disease, musculoskeletal disease, and cardiac disease. PET and PET/CT: A Clinical Guide, Third Edition by world renowned molecular imaging pioneer Abass Alavi and esteemed diagnostic and nuclear radiologist Eugene Lin features the latest advances in PET technology in an easy-to-read format. The book lays a solid foundation with opening chapters on scanner physi